The Efficacy of Lactulose for the Treatment of Hyperammonemic Encephalopathy Due to Severe Heart Failure - Koichi Narita; Eisuke Amiya; Nobutaka Kakuda; Hidehiro Kaneko; Masaru Hatano; Issei Komuro (Diagnostics, 2020)
Hyperammonemic encephalopathy secondary to heart failure is rare and there had been little reports about effective treatment. Organ hypoperfusion or congestion by heart failure may lead to various organ dysfunctions, and liver and intestinal circulatory impairment might cause ammonia metabolic failure. Here, we report on the case of a patient with hyperammonemic encephalopathy that was secondary to heart failure, which was effectively treated by lactulose.